Evaluasi penganggaran, pengalokasian, penyaluran, penatausahaan, pertanggungjawaban dan pelaporan dana desa pada Desa Pineleng Satu Timur dan Pineleng Dua Indah - Zeke, Aurora Christi; Afandi, Dhullo; Pinatik, Sherly (Riset Akuntansi dan Portofolio Investasi, 2024)
The village fund can create development and empower villages toward a fair, prosperous, and prosperous society. This study aims to evaluate the processes of Budgeting, Allocation, Distribution, Administration, Accountability, and Reporting of Village Funds in the villages of Pineleng Satu Timur and Pineleng Dua Indah to determine whether they are adequate or not by examining their compliance with prevailing regulations and the theory of the Government's Internal Control System. The method used in this research is a qualitative descriptive method. The results show that the processes of Budgeting, Allocation, Distribution, Accountability, and Reporting of Village Funds in Pineleng Satu Timur and Pineleng Dua Indah villages are in accordance with the prevailing regulation, namely PMK Number 201/PMK.07/2022 concerning the Internal Control System. However, the administration process of the village funds in these villages cannot yet be considered compliant with the prevailing regulations. The budgeting to reporting processes of the village funds in both villages can be deemed adequate, considering the presence of elements of the Internal Control System in each stage from budgeting to reporting of the village funds.